(3EbJUGOjGJ fXe GdeYdheGJ GdeMGSHjI hGdEOGQjI (B/s - (3eHGQc, UdGM GdOjf YHO GdefYes ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2001)
(3OQGSI eaghe GdeYdheGJ hYdGbJg HfXGe GdeYdheGJ GdeMGSHj ddeTQhYGJ(B- (3feGPL GdJcdaI hGdefaYI dCfXeI GdeYdheGJ GdeMGSHjI(B- (3GdEWGQ GdTGed dJbjje CfXeI GdeYdheGJ GdeMGSHjI(B.s
Keywords: (3GdEOGQIs; (3GdeMGSHIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s